Analysis of Physicochemical Characteristics Diversity of 46 Accessions of Indonesian Local Rice Germplasms - Septian D.W. Putra; Elis Septianingrum (Universitas PGRI Semarang, 2019)
Physicochemical characterization of rice germplasms is an important step of the rice breeding program. The physicochemical characteristics are important for consumers’ acceptance. The objective of this study was to analyze physicochemical characteristics information to obtain suitable accessions for breeding programs and to cluster accessions according to their main characteristics. A total of 46 accessions of ICRR & ICABIOGRD collection were evaluated for 24 physicochemical traits. Principal component Analysis (PCA) was carried out to analyze the variation and the contribution of each trait to the total variance. This study showed that physicochemical variation might be divided into 5 principal component: Principal component 1 (PC1) was dominated by grain roundness, PC2 by low amylose content, PC3 by high milling yield, PC4 by long and slender grain, and PC5 by premium quality. Clustering analysis yielded 4 clusters. The 1st cluster was dominated by round grain, 2nd cluster by low milling yield, 3rd by high broken grain, and the last cluster by high milling yield and premium quality. This work showed that there were 7 potential accessions to be included in the rice breeding program of high milling yield and premium quality rice, i.e. accession no. 10479 (Umbul-umbul), 10486 (Babad Cianjur), 10491 (Marus), 10499 (619), 10515 (Siregi), 10551 (Logawa), and 10562 (Umbul-umbul). Those varieties can be used by rice breeders to develop new varieties to answer the global challenge of food security.